2013
DOI: 10.1002/bit.24929
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated bioprocessing of highly concentrated jerusalem artichoke tubers for simultaneous saccharification and ethanol fermentation

Abstract: Consolidated bioprocessing (CBP) of Jerusalem artichoke tuber (Jat) for ethanol production is one of the most promising options for an alternate biofuel technology development. The technical barriers include the weak saccharolytic enzyme (inulinase) activity of the fermentation strain, and the well mixing of the high viscous fermentation slurry at the highly concentrated Jat loading. In this study, Saccharomyces cerevisiae DQ1 was found to produce relatively large amount of inulinase for hydrolysis of inulin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Under their experimental conditions, these two strains gave 90% and 79.7% of theoretical ethanol yield respectively at 40 °C within 84 h fermentation. Very recently, Guo et al [161] reported an improved CBP process in a helical ribbon stirring bioreactor using mutant yeast, S. cerevisiae DQ1. The ethanol concentration was as high as 128 g/L, which is very promising.…”
Section: Bioproducts Derived From Jerusalem Artichokementioning
confidence: 99%
“…Under their experimental conditions, these two strains gave 90% and 79.7% of theoretical ethanol yield respectively at 40 °C within 84 h fermentation. Very recently, Guo et al [161] reported an improved CBP process in a helical ribbon stirring bioreactor using mutant yeast, S. cerevisiae DQ1. The ethanol concentration was as high as 128 g/L, which is very promising.…”
Section: Bioproducts Derived From Jerusalem Artichokementioning
confidence: 99%
“…Yeast strains expressing high levels of inulases have been developed and successfully used for ethanol production from Jerusalem artichoke [31]. However, not very biotransformation can be achieved by inulaseproducing strains.…”
Section: Comparison Of Acid and Enzymatic Hydrolysis Of Water-extractmentioning
confidence: 99%
“…Relatively new studies employed the CBP approach for ethanol production using JA tuber flour. In these studies, tubers were washed, cut or chopped in a grinder, dried, and then milled to obtain tuber flour (Yuan et al, 2008;Liu et al, 2011;Guo et al, 2013;Sarchami and Rehmann, 2014;Khatun et al, 2016). In two studies, dried slices (Yuan et al, 2013b) or tuber mash after grinding (Charoensopharat et al, 2015) were the source of inulins.…”
Section: Fermentation Of Sugars From Tubers Of Jamentioning
confidence: 99%
“…This resulting strain JZD-InuMKCP showed highest ethanol productivity of 3.2 g/L/h in 24 h and 2.44 g/L/h in 36 h with 95% theoretical ethanol yield solely fermented on JA tuber flour. Guo et al (2013) used engineered S. cerevisiae DQ1 for CBP at optimum conditions of 30°C and pH 5.5. The optimum activity of the inulinase from this strain was at 50-55°C and pH 5.0.…”
Section: Fermentation Of Sugars From Tubers Of Jamentioning
confidence: 99%